Afterdischarges of Spinal Interneurons Following a Brief High-Frequency Stimulation of Ia Afferents in the Cat - Méndez-Fernández, Abraham; Moreno-Castillo, Mayra; Huidobro, Nayeli; Flores, Amira; Manjarrez, Elias (Frontiers in Integrative Neuroscience, 2020)
Spinal motoneurons exhibit sustained afterdischarges and plateau potentials following a brief high-frequency stimulation of Ia afferents. Also, there is evidence that spinal cord interneurons exhibit plateau potentials. However, to our knowledge, there are not reports about the possible afterdischarge behavior of lumbar spinal interneurons activated by Ia afferents. Given that there are spinal interneurons receiving monosynaptic inputs from Ia afferents, then these cells could be activated in parallel to motoneurones after repetitive muscle stretch. We explored this possibility in cats with a precollicular-postmammillary decerebration. We found that a brief high-frequency stimulation of Ia afferents produces afterdischarges that are highly correlated to a DC slow potential recorded at the cord dorsum. We conclude that in the cat spinal cord, not only the motoneurons but also the interneurons from the superficial and deep dorsal horn produce sustained afterdischarges, thus highlighting the importance of interneurons in the spinal neuronal circuitry. The significance of our finding is that it opens the possibility that the spinal cord interneurons activated by Ia afferents could also exhibit bistability, a relevant phenomenon well characterized in the motoneurons.